Vibrodiagnostic of aircraft hydraulic emergency hydrogenerator NP 27T. (August 2022) - Sloboda, Aurel; Piľa, Jan; Sloboda, Oskar; Sloboda, Aurel; Korba, Peter; Hovanec, Michal; Rácek, Branislav
Highlights: The main requirement for the aircraft operation is high level of flight safety. The method is based on quantitative methods by measuring physical parameters. Vibrodiagnostic as a possibility to check the wear of hydrogenerator parts. Abstract: The safety of operation and the extension of the aircraft life cycle cannot be ensured without the use of methods and means of technical diagnostics. Monitoring and diagnostics of the technical condition of aircraft components is therefore one of the most important task. The main problem being addressed is the monitoring of the manifestations of the incipient degradation of piston hydraulic pumps, which are critical elements in terms of flight safety. The main research question is: what changes in the physical parameters occur in the process of degradation of the hydraulic pump components and how they affect the life cycle of the pump? The research methodology is based on quantitative methods of data obtained by measuring the physical parameters of the pump such as vibration, acoustic emissions, flow and fluid pressure and temperature. The obtained results show that there is agreement of the initial degradation manifestations, but only for certain physical parameters of the hydraulic pump. This finding is significant in that the outlet pressure from the pump does not necessarily signal the initial stage of its degradation. From the point of view of the safety of the hydraulic system and the mission of the aircraft, we consider this to be an important and originality knowledge.